Understanding developmental language disorders: From theory to practice - Norbury, C; Tomblin, J; Bishop, D (Psychology Press Taylor and Francis Group, 2008)
Developmental language disorders (DLD) occur when a child fails to develop his or her native language often for no apparent reason. Delayed development of speech and/or language is one of the most common reasons for parents of preschool children to seek the advice of their family doctor. Although some children rapidly improve, others have more persistent language difficulties. These long-term deficits can adversely affect academic progress, social relationships and mental well-being. Although DLDs are common, we are still a long way from understanding what causes them and how best to intervene. Understanding Developmental Language Disorders summarises the recent research developments in genetics and neuroimaging studies, assessment techniques and treatment studies to provide an overview of all aspects of DLD. The book investigates the possible genetic and biological causes of the disorder, how best to assess children's language skills to identify when and where communication breakdown occurs, what the long-term outcomes are for children who grow up with DLD, overlaps between DLD and other childhood disorders such as dyslexia and autism and how best to treat children with the disorder. Each chapter is written by a leading authority in the field in a format accessible to researchers, clinicians and families alike. This book, with its focus on both theory and practice, will be invaluable to students and researchers of speech-language pathology, psychology, psychiatry, linguistics and education. It will also be of interest to practicing speech-language pathologists, clinical psychologists, psychiatrists, educational psychologists, and teachers and parents of children with developmental language disorders.